(untitled) (Eurasian Research Bulletin, 2022)
In this article Scutellaria adenostegia Briq. information about the phytosenotic and ontogenetic description of the plant in the Fergana Valley is given. For the first time in the course of research, S.the demographic indicators of adenostegia in the various cenopopulias distributed in the Fergana Valley have been studied